Language and social cognition : expression of the social mind - Pishwa, Hanna (Trends in linguistics. Studies and monographs ;, 2009)
In a collection of 16 papers, eminent scholars from several disciplines present diverse and yet cohering perspectives on the expression of social knowledge, its acquisition and management. Hence, the volume is an attempt to view the social functions of language in a novel, systematic way. Such an approach has been missing due to the complexity of the matter and the emphasis on purely cognitive properties of language. The volume starts with a presentation of overarching issues of the social nature of humans and their language, providing strong evidence for the social fundaments of human nature a.